Marginal zone B cells exacerbate endotoxic shock via interleukin-6 secretion induced by Fcα/μR-coupled TLR4 signalling - 藤本 学; 小田 ちぐさ; 田原 聡子; 渋谷 和子; 渋谷 彰; Honda Shin-ichiro; Sato Kazuki; Totsuka Naoya; Fujiyama Satoshi; Fujimoto Manabu; Miyake Kensuke; Nakahashi-Oda Chigusa; et al. (Nature communications, 2016)
Marginal zone (MZ) B cells produce a first wave of antibodies for protection from blood-borne pathogens. However, the role of MZ B cells in inflammatory responses has not been elucidated. Here we show that MZ B cells produce pro-inflammatory cytokines, such as interleukin-6 (IL-6), and exacerbate systemic inflammatory responses to lipopolysaccharide (LPS). After intravenous injection of LPS or E. coli, mice deficient in MZ B cells or IL-6 only in MZ B cells have attenuated systemic inflammatory responses and prolonged survival compared with wild-type mice. LPS directly stimulates MZ B cells via Toll-like receptor 4 (TLR4) and MyD88 pathways for IL-6 production. Furthermore, TLR4 requires physical and functional association with Fcα/μR (CD351) for its oligomer formation, NF-κB signalling and IL-6 production from MZ B cells; this association is responsible for systemic inflammatory responses and endotoxic shock. These results reveal a pro-inflammatory role of MZ B cells in endotoxic shock.